Developmental-Centered Care in Preterm Newborns: Scoping Review - Jina M. Velasco Arias; Aida M. Peres; Francisco M. Escandell Rico; M. Carmen Solano-Ruiz; Vicente F. Gil-Guillen; Ana Noreña-Peña (Children, 2025)
Background/Objectives: Preterm newborns often require specialized care and management. However, exposure to multiple stimuli during hospitalization can adversely affect their neurological development. Developmental-centered care integrates evidence-based practices and neuroprotective strategies to create an optimal care environment that minimizes harmful stimuli in the neonatal intensive care unit (NICU) and supports the neurological development of preterm infants. To identify interventions related to developmental-centered care that support preterm newborns in the NICU. Methods: A scoping review was conducted following the guidelines of the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews. A comprehensive search was performed in MEDLINE, CINAHL, and Web of Science databases. The results were categorized based on the general characteristics of the studies and the main interventions related to developmental-centered care. Results: Out of 163 potentially relevant sources identified, 19 studies met the inclusion criteria. A total of 52 interventions were identified and classified into three thematic categories related to the benefits of the kangaroo care method, the family-centered care model, and the neonatal individualized developmental care and assessment program. Conclusions: The findings underscore the importance of integrating developmental-centered care practices, such as skin-to-skin contact, specialized feeding, and active parental involvement, into clinical practice to support neurodevelopment and improve health outcomes in preterm infants.